Children’s Literature as Learning Media to Improve Children’s Language Skills - Uli Agustina Gultom; Inung Setyami (Universitas Sebelas Maret, 2022)
This article aims to describe children's literature as a means of learning language skills for children. Children's literature is literature aimed at children. Children's literature is literature that reflects the feelings and experiences of children through children's views on topics that are close to the child's world, including humans, fauna, and flora. Through literature, a child indirectly learns language skills as well. Children's literature is also important because it teaches young learners a variety of lessons. It also gives them opportunities to engage with literature; teaches them an appreciation for their cultural heritage; fosters emotional intelligence and creativity; fosters the growth and development of the children’s personality and social skills; and conveys important literature from one generation to the next. Children's literature needs to be developed and taught from an early age so that young learners have good personalities and are knowledgeable. It can be a valuable resource, particularly in language teaching. Learning language skills is applied through the introduction of three literary genres, namely: 1) poetry in the form of children's songlines and children's rhymes; 2) prose in the form of fantasy fairy tales and folk tales; and 3) drama in the form of stories with simple dialogues.